Manipulating the Lewis antigen specificity of the cholesterol-dependent cytolysin lectinolysin - Lawrence, Sara; Feil, Susanne; Holien, Jessica; Kuiper, Michael; Doughty, Larissa; Dolezal, Olan; Mulhern, Terrence; Tweten, Rodney; Parker, Michael (Frontiers in Immunology, 2012)
The cholesterol-dependent cytolysins (CDCs) attack cells by punching large holes in their membranes. Lectinolysin from Streptococcus mitis is unique among CDCs due to the presence of an N-terminal lectin domain that enhances the pore-forming activity of the toxin. We recently determined the crystal structures of the lectin domain in complex with various glycans. These structures revealed the molecular basis for the Lewis antigen specificity of the toxin. Based on this information we have used in silico molecular modelling to design a mutant toxin, which we predicted would increase its specificity for Lewis y, an antigen found on the surface of cancer cells. Surprisingly, we found by surface plasmon resonance binding experiments that the resultant mutant lectin domain exhibited higher specificity for Lewis b antigens instead. We then undertook comparative crystallographic and molecular dynamics simulation studies of the wild-type and mutant lectin domains to understand the molecular basis for the disparity between the theoretical and experimental results. The crystallographic results revealed that the net number of interactions between Lewis y and wild-type versus mutant was unchanged whereas there was a loss of a hydrogen bond between mutant and Lewis b compared to wild-type. In contrast, the molecular dynamics studies revealed that the Lewis b antigen spent more time in the binding pocket of the mutant compared to wild-type and the reverse was true for Lewis y. The results of these simulation studies are consistent with the conclusions drawn from the surface plasmon resonance studies. This work is part of a program to engineer lectinolysin so that it will target and kill specific cells in human diseases.